LAMDIK Policy and Its Impact on Education Quality - Nuryana, Amiatun; Setya Yuwana; Rachmawati Novaria; Handoko, V. Rudy (Universitas Medan Area, 2025)
This study analyzes the challenges, solutions, and impact of the LAMDIK policy on educational quality at UIN Sunan Ampel Surabaya. The research uses Edward III's policy implementation theory to highlight the importance of communication, resources, implementer attitudes, and bureaucratic structures in policy execution. A qualitative descriptive method was applied through case studies, including observation, in-depth interviews, and document analysis with triangulation. The findings reveal several challenges in implementing the policy within the Early Childhood Islamic Education Study Program, such as limited human resources, inadequate facilities, curriculum issues, weak internal quality assurance, and insufficient external collaboration. Strategies to address these include improving lecturer competence, regular quality monitoring, and expanding institutional partnerships. The policy implementation has contributed to higher educational standards, stronger institutional capacity, and the development of a continuous quality assurance culture.